2003
DOI: 10.1248/bpb.26.481
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Methanol Extract from the Aerial Parts of Saururus chinensis on Lipopolysaccharide-Induced Nitric Oxide and Prostagladin E2 Production from Murine Macrophage RAW 264.7 Cells.

Abstract: As an attempt to search for bioactive natural products exerting antiinflammatory activity, we have evaluated the effects of the methanol extract from the aerial parts of Saururus chinensis (LOUR.) BAILL (Saururaceae) on lipopolysaccharide (LPS)-induced nitric oxide (NO) and prostaglandin E 2 (PGE 2 ) release by the macrophage cell line RAW 264.7. Our data indicate that this extract is a potent inhibitor of NO production and it also significantly decreased PGE 2 release. Consistent with these observations, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…31,32) For iNOS enzymatic reaction, the cells were stimulated with LPS for 12 h followed by two washes with phosphate buffered saline (PBS). These pre-stimulated cells were incubated in the presence or absence of DP-C for a further 12 h without LPS.…”
Section: Reagentsmentioning
confidence: 99%
“…31,32) For iNOS enzymatic reaction, the cells were stimulated with LPS for 12 h followed by two washes with phosphate buffered saline (PBS). These pre-stimulated cells were incubated in the presence or absence of DP-C for a further 12 h without LPS.…”
Section: Reagentsmentioning
confidence: 99%
“…Its aerial portion has been used in Korean folk medicine for the treatment of edema, gonorrhea, jaundice, and several inflammatory diseases. 10) Studies have shown that S. chinensis has various activities, including anti-inflammatory, anti-oxidant, 11,12) antiangiogenic, 13) anti-asthmatic, 14) and anti-hypertensive 15) activities, as well as therapeutic activity against atopic dermatitis. 16) Among the bioactive compounds isolated from S. chinensis, manassantin A is a major phytochemical composition that has various biological activities, including anti-inflammatory, neuroleptic, and human acyl-CoA : cholesterol acyltransferase (ACA T) inhibitory activities.…”
mentioning
confidence: 99%
“…Several studies have reported that the ethanol extract of S. chinensis Baill (SC-E) decreased inflammation by inhibiting intracellular nitric oxide, prostaglandin E2, and various inflammatory cytokines released by lipopolysaccharide stimulation of raw 264.7 macrophages (Kim et al, 2003;Yoo et al, 2008;. SC-E also regulated blood lipid level in animal model and suppressed the activity of a-glucosidase for the anti-diabetic effect (Hwang et al, 2007;Yu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%